2017
DOI: 10.1016/j.alcohol.2017.02.179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate alcohol consumption on gene expression related to colonic inflammation and antioxidant enzymes in rats

Abstract: Excessive alcohol consumption is a risk factor associated with colorectal cancer; however, some studies have reported that moderate alcohol consumption may not contribute additional risk for developing colorectal cancer while others suggest that moderate alcohol consumption provides a protective effect that reduces colorectal cancer risk. The purpose of this study was to determine the effects of moderate voluntary alcohol (20% ethanol) intake on alternate days for 3 months in outbred Wistar rats on risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The mechanisms by which alcohol consumption influences CRC risk are still being explored . The breakdown of alcohol to acetaldehyde, a carcinogen that has been shown to disrupt DNA replication and repair, is widely believed to play a role in CRC risk .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanisms by which alcohol consumption influences CRC risk are still being explored . The breakdown of alcohol to acetaldehyde, a carcinogen that has been shown to disrupt DNA replication and repair, is widely believed to play a role in CRC risk .…”
Section: Discussionmentioning
confidence: 99%
“…17 The mechanisms by which alcohol consumption influences CRC risk are still being explored. 13,14,29 The breakdown of alcohol to acetaldehyde, a carcinogen that has been shown to disrupt DNA replication and repair, is widely believed to play a role in CRC risk. 14,30,31 Chronic alcohol consumption has also been shown to disrupt folate metabolism, and folate deficiency is an established risk factor for CRC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, investigations in rats fed a high-fat high-cholesterol diet showed that a moderate ethanol consumption for 8 weeks alleviated liver fibrosis and reduced the mRNA expression of several profibrotic genes [18]. Notably, the beneficial effects of moderate ethanol exposure in rodents are not restricted to the liver and can also be observed in other organs and tissues such heart, colon, white adipose tissue and blood vessels [19][20][21]. Lower oxidative stress and inflammation as well as improvement of lipid metabolism could be involved in these favorable effects [19][20][21].…”
Section: Introductionmentioning
confidence: 99%